Mild COVID-19 despite autoantibodies against type I IFNs in autoimmune polyendocrine syndrome type 1 - Meisel, Christian; Akbil, Bengisu; Meyer, Tim; Lankes, Erwin; Corman, Victor M.; Staudacher, Olga; Unterwalder, Nadine; Kölsch, Uwe; Drosten, Christian; Mall, Marcus A.; Kallinich, Tilmann; Schnabel, Dirk; et al. (The Journal of clinical investigation, 2021)
Autoantibodies against IFN-α and IFN-ω (type I IFNs) were recently reported as causative for severe COVID-19 in the general population. Autoantibodies against IFN-α and IFN-ω are present in almost all patients with autoimmune polyendocrine syndrome type 1 (APS-1) caused by biallelic deleterious or heterozygous dominant mutations in AIRE. We therefore hypothesized that autoantibodies against type I IFNs also predispose patients with APS-1 to severe COVID-19. We prospectively studied 6 patients with APS-1 between April 1, 2020 and April 1, 2021. Biobanked pre-COVID-19 sera of APS-1 subjects were tested for neutralizing autoantibodies against IFN-α and IFN-ω. The ability of the patients' sera to block recombinant human IFN-α and IFN-ω was assessed by assays quantifying phosphorylation of signal transducer and activator of transcription 1 (STAT1) as well as infection-based IFN-neutralization assays. We describe 4 patients with APS-1 and preexisting high titers of neutralizing autoantibodies against IFN-α and IFN-ω who contracted SARS-CoV-2, yet developed only mild symptoms of COVID-19. None of the patients developed dyspnea, oxygen requirement, or high temperature. All infected patients with APS-1 were females and younger than 26 years of age. Clinical penetrance of neutralizing autoantibodies against type I IFNs for severe COVID-19 is not complete.